Barium hexaferrite thick films prepared by screen printing for microwave applications. (November 2015) - Zhang, W. L.; Wang, R.; Peng, B.; Huang, Z. L.; Zhang, W. X.
Abstract : In this work, hexagonal barium ferrite thick films with a thickness of about 90 μm were prepared on alumina substrates by screen printing method. Microstructure and magnetic properties of the thick films have been studied. The results show that organic vehicles have a great influence on the microstructure of the ferrite thick films. It is found that the density and surface flatness of the barium ferrite thick films can be improved greatly by hot-press sintering process. The barium ferrite films prepared by hot-press sintering show a clear magnetic anisotropy. Along the easy axis, the squareness ratio of the hexagonal barium ferrite thick films is about 0·75 with a coercive field of 3·4 kOe. A prototype of microwave circulator with the prepared BaM thick films was fabricated.